Host-vector system for phenol-degrading Rhodococcus erythropolis based on Corynebacterium plasmids - Veselý, M; Pátek, M; Nesvera, J; Cejková, A; Masák, J; Jirků, V (Applied microbiology and biotechnology, 2003)
The strain Rhodococcus erythropolis CCM2595, which was shown to degrade phenol, was chosen for genetic studies. To facilitate strain improvement using the methods of gene manipulation, the technique of genetic transfer was introduced and cloning vectors were constructed. Using the plasmid pFAJ2574, an electrotransformation procedure yielding up to 7x10(4) transformants/microg DNA was optimized. Escherichia coli- R. erythropolis shuttle vectors were constructed using the replicons pSR1 and pGA1 from Corynebacterium glutamicum. The small vector pSRK21 (5.8 kb) provides six unique cloning sites and selection of recombinant clones using alpha-complementation of beta-galactosidase in E. coli. This vector, exhibiting high segregational stability under non-selective conditions in R. erythropolis CCM2595, was applied to cloning and efficient expression of the gene coding for green fluorescent protein (gfpuv).
Keywords: Transformation, Genetic; exprese genu; DNA bakterií; transformace genetická; sekvence nukleotidů; Corynebacterium; genetické vektory; zelené fluorescenční proteiny; Gene Expression; biodegradace; klonování DNA; fenol; Green Fluorescent Proteins; Phenol; Escherichia coli; Recombinant Proteins; plazmidy; replikon; Biodegradation, Environmental; Rhodococcus; rekombinantní proteiny; DNA, Bacterial; Base Sequence; Luminescent Proteins; Chromosome Mapping; Replicon; Genetic Vectors; mapování chromozomů; luminescentní proteiny; Cloning, Molecular; Plasmids